Fatherless dan Konsep Diri pada Remaja Di Kota Makassar yang Berasal dari Keluarga Tidak Utuh - Rumorati, Jane Prisilia Batara; Ridfah, Ahmad; St. Hadjar Nurul Istiqamah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Teenagers with incomplete families tend to have difficulty building good social relationships. This condition is caused by a divided family, resulting in the absence of the father's role and children tending to have a negative self-concept. This research aims to determine the relationship between fatherlessness and self-concept among teenagers in Makassar City who come from incomplete families. The method used in this research is a quantitative survey method with the number of research respondents being 300 teenagers from incomplete families in Makassar City. This research uses measuring instruments in the form of a fatherless scale with a Cronbach alpha reliability value of 0.980 and a self-concept scale with a Cronbach alpha reliability value of 0.864. The data analysis used was the non-parametric Spearman's rho statistic with the help of JASP v0.16.2.0 for Windows. The results of data analysis produced a value of r= -0.550 and p>0.001. These results show that there is a very significant negative relationship between fatherlessness and self-concept in adolescents who come from incomplete families. The higher the fatherlessness, the lower or negative the adolescent's self-concept. It is hoped that the research results will become a source of information for teenagers and parents to increase the presence of the father's role so that teenagers' self-concept becomes more positive and avoid negative self-concept caused by the absence of the father's role. The results of this study have implications for the importance of institutions related to marriage preparation and strengthening the role of the family to provide socialization materials on the role of fathers and mothers to prospective couples and young families.